Pengaruh Media Video Animasi terhadap Pengetahuan Remaja tentang Perilaku Seks Beresiko di SMA Negeri 10 Kota Jambi - Ry Eny Mian Marisi Br. Simanjuntak; Verawati Pulungan; Wilma Wilma; Rosyati Pastuty; Ajeng Galuh Wuryandari (Jurnal Akademika Baiturrahim Jambi, 2026)
One of the problems that occurs during adolescence is risky sexual behavior. This problem tends to be carried out by groups of teenagers aged 15-21 years. Risky sexual behavior can have impacts, including pregnancy at a young age. Currently the incidence of teenage pregnancy in Indonesia is 48 per 1,000 women. Survey results (2020) show that teenagers in Jambi Province who commit sexual acts are at risk of 68.1%, risky sex for teenagers consists of holding hands and being embraced by a boyfriend 42.2%, lip kissing 23.1%, petting and intercourse 2.8%. This deviation in sexual behavior occurs as a result of the adolescent's lack of ability to exercise self-control caused by a lack of knowledge about the impacts resulting from their sexual behavior and understanding of religion and applicable norms. This research aims to determine the influence of health promotion using animated video media on adolescent knowledge about risky sexual behavior. This research is pre-experimental research with One-Group Pretest-Posttest Design. This research was conducted at SMA Negeri 10 Jambi City with a population of 216 people, a sample of 63 participants. Data collection was carried out using questionnaires, then analyzed univariately and bivariately using the wilcoxon test. The results showed that the mean knowledge score of the respondents before the intervention was 4.75 and after the intervention, the mean knowledge score of the respondents was 9.22. It can be concluded that there is an influence of health promotion using animated video media on teenagers' level of knowledge about risky sexual behavior with a score of ⁇ 0.001. It is hoped that further research can be carried out with the development of better reproductive health animated video media and different materials so that teenagers are more responsible for their reproductive health